A Fish Chorus on the Margin of New Jersey Atlantic Continental Shelf - Zhang, Qianchu; Katsnelson, Boris (Frontiers in Marine Science, 2021)
We report herein an underwater biological chorus coming from the margin of the New Jersey Atlantic continental shelf that we tentatively attribute to a species of fish. The chorus occurred every night for over a month during the Shallow Water 2006 experiment and covers the frequency band 150–4,800 Hz, with maximum intensity in the band from 1450 to 2,000 Hz. Remarkable intensity peaks occurred at 500, 725, 960, 1,215, 1,465, 1,700, and 1,920 Hz, rising to as much as 20 dB above the background noise without the chorus. The chorus begins at sunset and reaches its maximum intensity within an hour, following which it weakens slightly and then gradually climbs again to a peak before sunrise, at which point it quickly weakens and disappears. Its frequency-domain characteristics and the nocturnal timing are reminiscent of sound produced by underwater animals. The intensity of the chorus weakens along the across-shelf path going shoreward, which indicates that the chorus originates from the margin of the continental shelf rather than from the coastal zone, as is generally considered. The chorus contains a single type of acoustic signal that takes the form of double-pulse bursts that last about 8.7 ms, with each pulse containing several acoustic cycles. The time interval between successive bursts varies from 1.5 to 1.9 s. Signals containing a number of bursts vary in length from tens to hundreds of seconds. Although it is impossible to determine the fish species responsible for the chorus, its characteristics, including its low frequency and intensity, its single type of short-duration sound signal, and its multiple peaks in the frequency domain, are all consistent with the general characteristics of fish sounds.